The Mediating Effect of Risk Awareness on the Relationship Between Infectious Disease Knowledge and Protective Behaviors Among Earthquake-Affected Populations - Selda Seçginli; Nesrin İlhan; Gizemnur Torun; Merve Altıner Yaş; Seda Doğru Bolat (Healthcare, 2026)
Background: Long-term post-disaster settings increase infectious disease risks, requiring adequate knowledge and risk awareness to promote protective behaviors. This study was conducted to investigate the relationships between infectious disease knowledge, risk awareness, and protective behaviors among earthquake-affected individuals, and to test the mediating effect of risk awareness on these relationships. Methods: This cross-sectional study was conducted among 257 participants living in two container settlements in an earthquake-affected region. Data were collected with the Sociodemographic Information Form, the Infectious Disease Knowledge Questionnaire (IDKQ), and the Communicable Diseases Risk Awareness and Protection Scale (CDRAPS). Data were analyzed using descriptive statistics, t-tests, ANOVA, Pearson’s correlation analysis, and the mediating effect of risk awareness was tested using Hayes’ PROCESS macro (Model 4). Results: The mean scores of the IDKQ and CDRAPS were 8.69 ± 5.82 and 131.50 ± 24.49, respectively. Significant positive correlations were found between IDKQ scores and CDRAPS total and subdimension scores (p < 0.001). Self-Protection Awareness significantly mediated the relationship between infectious disease knowledge and both Protection Behaviors (β = 0.420, 95% CI [0.299–0.557]) and Handwashing Behaviors (β = 0.104, 95% CI [0.050–0.161]). Personal Contact Awareness significantly mediated the relationship between infectious disease knowledge and Protection Behaviors (β = 0.256, 95% CI [0.117–0.388]) as well as Handwashing Behaviors (β = 0.172, 95% CI [0.118–0.221]). Conclusions: Greater infectious disease knowledge was associated with higher protective behaviors, and this association was partially mediated by self-protection awareness and personal contact awareness. Interventions aimed at improving infectious disease knowledge and awareness may contribute to strengthening individuals’ protective and handwashing behaviors.